: تطور دلالات المصطلح الطبي في حقل الأمراض بين معجم العين ومعجم تاج العروس دراسة تحليلية مقارنة - برواني، سعيد أحمد سعيد (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The present research deals with the connotations of the medical term in one of its special aspects, focusing on a field of it, which is the field of diseases. Old dictionaries have abounded with many of them on all public and private levels, and some of them have even been moved from purely linguistic level to scientific terminological level. This research aims to unveil the development of these terms by taking different terms from the fields compatible with diseases and historically studying their linguistic development, since their existence in the first dictionary, which is Al-Ain by Khalil bin Ahmed Al-Farahidi to the Taj Al-Arous dictionary by Al-Zubaidi, narrowly restricted to terms common to both dictionaries. The researcher has followed the descriptive, analytical, and comparative approach. This approach is employed to track the similarities and differences, and to determine the extent of this similarity or difference between the older dictionary and the latter dictionary by relying on parallel semantic fields. Through this approach, it is possible to determine the semantic development of medical terms in the field of diseases. This research has obtained important results, most important of which is that the utterance "term" was not consistent for ancient linguists, and it did not appear until late in the eighth Hijri century. The utterance "convention" initially appeared with Al-Jurjani in his book Alta'rifat (the definitions), while generalization and specification did not acquire their modern indication in the old dictionaries, but they instead gained meaning through context. Words close in meaning were used to denote both. Their meanings evolved in dictionaries of meanings and terms until they became terms indicative of critical, verbal, and astronomical sciences. Western and Arab semantics scholars have had the most prominent role in forming and marking the semantic development of generalization and specification. The number of words in which semantic transition took place was larger than of words that underwent generalization and specification. Moreover, transitions of semantic referencing had varied aspects of semantic developments, which occurred through linguistic and non-linguistic means in accordance with utterances undergoing semantic development. The development of these semantics’ development did not exceed the fifth century in the entirety of words addressed in this research, and some of these words remained with their semantics referencing, and they were never transferred onto medical books. Some of them were transferred onto the medical field with modern connotations, while some others remained in their linguistic field and were never transferred to the medical field. This applies to modern translation of these terms, as the word has been affected by fluctuations in the transition from the linguistic field to the medical field.